FACTORS OF USING THE NATIONAL PEDAGOGICAL EXPERIENCE OF "EDUCATION WORK". - Ismailova, Dilafruz (Журнал иностранных языков и лингвистики, 2022)
The article discusses the factors of using the domestic pedagogical experience of "Educational work"